Consequences of unpaid blood plasma donations - Axel Ockenfels; Alvin E. Roth (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2023)
The European Commission is considering new ways to regulate the 'substances of human origin' - including blood, plasma, and cells - used in medical procedures from transfusions and transplants to assisted reproduction. This column argues that such legislation jeopardises the interests of both donors and recipients. While sympathetic to the intentions behind the proposals - which aim to ensure that donations are voluntary and to protect financially disadvantaged donors - the authors believe such rules overlook the effects on donors, on the supply of such substances, and on the health of those who need them.
Keywords: 330